2020
DOI: 10.1186/s40359-020-00414-4
|View full text |Cite
|
Sign up to set email alerts
|

Is there prejudice from thin air? Replicating the effect of emotion on automatic intergroup attitudes

Abstract: Background: Previous studies showed that anger, rather than sadness, created automatic intergroup bias in a minimal group context. Methods: The current research reports a single study (N = 99) aiming to replicate this finding and further to test whether the intergroup bias manifests as ingroup favoritism, outgroup derogation, or both. Results: Our results failed to replicate the effect of anger on automatic bias. Intriguingly, participants across all emotion conditions exhibited high level of ingroup favoritis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Nevertheless, several studies have revealed that individuals, in general, invest more money in the within-group pool than in the between-group pool [12,[32][33][34][35]. The same pattern has also been observed in studies in which researchers modi ed the game to encourage investment in the between-group pools [36][37][38][39][40][41]. Their ndings offer con icting evidence for the CO model: the empirical evidence does not suggest that individuals simultaneously acquire the tendency for in-group cooperation and out-group aggression.…”
Section: Coevolutionary Model Of Intergroup Biasmentioning
confidence: 68%
“…Nevertheless, several studies have revealed that individuals, in general, invest more money in the within-group pool than in the between-group pool [12,[32][33][34][35]. The same pattern has also been observed in studies in which researchers modi ed the game to encourage investment in the between-group pools [36][37][38][39][40][41]. Their ndings offer con icting evidence for the CO model: the empirical evidence does not suggest that individuals simultaneously acquire the tendency for in-group cooperation and out-group aggression.…”
Section: Coevolutionary Model Of Intergroup Biasmentioning
confidence: 68%
“…Stereotypes toward immigrants were measured using a semantic differential scale [45,46]. The scale contained five pairs of opposite adjectives, such as "pleasant-unpleasant" and "good-bad", rated on a seven-point Likert scale (1: Positive; 7: Negative).…”
Section: Methodsmentioning
confidence: 99%
“…Several research articles have proven that nurses experience high levels of stress and anxiety during COVID-19. Anxiety was assessed in 89.7% of Iranian nurses, as was stress in 54.9% of them [ 6 ]. Huang et al [ 7 ] found that out of 1,257 health workers caring for COVID-19 patients in 34 hospitals in China, 50% experienced depressive symptoms and 45% ran into anxiety.…”
Section: Introductionmentioning
confidence: 99%